"But with this I'm embodied": H.D.'s public photographic portraits, 1913–1956. Issue 1 (2nd January 2021) - Parker, Sarah; French, Jade
ABSTRACT: Questions of image were intensely important to H.D. Whether through the precise Imagism of her early poetry or her later work in cinema, H.D.'s career involved a lifelong engagement with image-making. But one important aspect of this has been overlooked: H.D.'s photographic portraiture. This article reveals that photography was central to H.D.'s authorial self-fashioning. Our article analyzes and contextualizes H.D.'s public photographic portraits from the 1910s to the 1950s, revealing how H.D. constructed her authorial persona along visual as well as textual lines, adapting her image across the decades. We concentrate on three key stages of H.D.'s emergence and re-emergence, centerd on particular creative periods: the launching of "H.D. Imagiste, " coinciding with her first published poems in 1913 and her debut volume Sea Garden (1916); the transition from muse to medusa as a result of H.D.'s cinematic apprenticeship in the 1920s and 1930s; and finally, H.D.'s re-emergence in the 1950s, in which she embraced her mature image as an androgynous prophetess, using this persona to promote her final works Helen in Egypt and Bid Me to Live (both 1960). We ultimately argue that H.D. developed a more empowering negotiation of aging, gender and public image compared to other female modernists.